Spectrophotometric Determination of Binding Constants of Ru(III) Salicylideneimine Complexes with CT DNA - Ljubijankić, Sead; Zahirović, Adnan; Memišević, Mahira; Ljubijankić, Nevzeta; Kahrović, Emira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
The interactions of Ru(III)  complexes with Schiff bases derived from salicylaldehyde and aminophenol, butylamine and naphthylamine with general formula Na[Ru(N-R-5-X-salim)2] (R = C6H4O, X = H, Cl, Br, NO2), Na[RuCl2(N-R-5-X-salim)2] (R = C4H9, X = H, Cl, Br, NO2) and [Ru(N-R-5-X-salim)3] (R = C10H7, X = H, Cl, Br) with CT DNA, were investigated by spectroscopic titration. Experimental data show that Ru(III) complexes with salicylideneimine bind CT DNA with constants of 104 M-1. The results indicate the influence of 5-X-substituents on Kb values.